Utilization of Yard Land to Support Food Security in Kandai Satu Village - Husnul Khatimah, Nur; Alkhair, Alkhair; Erham, Erham (AMK : Abdi Masyarakat UIKA, 2023)
Food security will continue to be a food problem in most countries in the world. This is because along with the increasing population, purchasing power and global climate dynamics also increase. Various kinds of efforts have been made to build food security both within the family and the wider community, one of which is by utilizing yards. The purpose of this community service program is for the community to be able to use their yards with productive plants for family food availability, increase family income, and medicine, and also effort to increase food security. Various social, cultural, and economic problems are still encountered in every program of utilizing community yards, including the not yet optimal use of yards, still part-time and not yet market-oriented, as well as a lack of assistance from officials who have not been adequate and evenly distributed. Therefore, careful planning and cross-sectoral support are needed in optimizing the use of yards so that they can contribute to supporting food security. Kandai Satu Sub-District is an area that has an average of yards belonging to the moderate to large yards group so that the utilization of yards can be done by combining various types of productive plants, including a combination of medicinal plants, fruits, vegetable plants, food plants, and other local plants. adapted to the size of the yard. Therefore, careful planning and cross-sectoral support are needed in optimizing the use of yards so that they can contribute to supporting food security. Kandai Satu Sub-District is an area that has an average of yards belonging to the moderate to large yards group so that the utilization of yards can be done by combining various types of productive plants, including a combination of medicinal plants, fruits, vegetable plants, food plants, and other local plants. adapted to the size of the yard. Therefore, careful planning and cross-sectoral support are needed in optimizing the use of yards so that they can contribute to supporting food security. Kandai Satu Sub-District is an area that has an average of yards belonging to the moderate to large yards group so that the utilization of yards can be done by combining various types of productive plants, including a combination of medicinal plants, fruits, vegetable plants, food plants, and other local plants. adapted to the size of the yard.